Perlindungan Hukum Terhadap Pekerja Mebel Kayu Berdasarkan Undang-Undang No.13 Tahun 2003 di Desa Batubulan (Studi Kasus di Yudiana Wood Carving) - Theo Sukardi Wibawa; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
National development needs manpower to assist development, fulfill needs, and work in wood processing companies to produce daily necessities from processed wood. The workforce must be considered, so in the Manpower Law, the legal protection provided is in the form of security, and work safety guarantees, and employers are required to provide work security tools. The formulation of the problems in this research, including 1) What is the form of legal protection for workers working at Yudiana Wood Carving Company according to Law Number 13 of 2003? 2) What is the responsibility of Yudiana Wood Carving Company to workers in the event of a work accident? This study uses the empirical method, with a statutory and conceptual approach. This study concludes that legal protection for workers who work at the Yudiana Wood Carving Company is the basic rights of workers such as safety protection, labor social security, and the responsibility of the Yudiana Wood Carving Company if workers have an accident at work by providing medical expenses and resolved amicably. Suggestions in this study are for the government to continue to monitor and follow up on companies that do not comply with statutory regulations.